Clinacanthus nutans lindau induced ros-dependent apoptosis and autophagy in HCT116 human colorectal cancer cells / Wang Kar Suen - Wang, Kar Suen (2018)
The practice of traditional medicine for cancer treatment and prevention is rising since the last decades. Clinacanthus nutans (Burm.f.) Lindau had been used traditionally for the treatment of inflammation, insect bites, snake bites, diabetes, herpes infection and cancer. This study aimed to investigate the apoptosis- and autophagy-inducing effects of C. nutans and the mechanisms of its effects in HCT116 human colorectal cancer cells. The MTT assay performed showed that C. nutans ethyl acetate fractions (CNEAF) exerted the strongest and dose-dependent cytotoxic effect against HCT116 cells with an IC50 value of 48.81±1.44 μg/mL among ethanol extract, hexane fraction, ethyl acetate fraction and aqueous fraction. Phosphatidylserine externalization, dissipation of mitochondrial membrane potential and nuclear morphological changes were observed in CNEAF-treated HCT116 cells suggesting the apoptosis induction effect of CNEAF. The results of western blot analysis demonstrated the upregulation of Bax and Bak along with the downregulation of Bcl-2 and Bcl-xL protein expressions further increased Bax/Bcl-2 ratio. Consequently, activation of initiator caspase-9, -8 and -10 followed by activation of caspase-3 were observed. This cascade was initiated by the death receptor DR5. Furthermore, CNEAF was found to exert autophagy-inducing effect as the accumulation of acidic vesicles, upregulation of autophagic proteins LC3 along with the downregulation of p62 were observed. CNEAF was found to increase the production of intracellular reactive oxygen species (ROS). Moreover, N-acetyl-cysteine (NAC), a ROS scavenger, abrogated CNEAF-induced apoptosis and autophagy in HCT116 cells. Lastly, GC-MS analysis of CNEAF indicated the presence of phytochemicals such as lupeol and stigmasterol. This study is the first to report that CNEAF induced ROS-dependent apoptosis and autophagy in HCT116 cells, suggesting that CNEAF can be developed as an alternative treatment for colorectal cancer.